Œuvrer en neurodidactique de la production d’écrits - Jocelyn REULIER (Éducation et Socialisation)
Faced with a growing number of pupils having a lot of difficulties in producing written work, we decided, with three primary school colleagues, to conduct a collaborative action-research which led to the creation of a module in « neurodidactics in written work ». In a collaborative, metacognitive process, our hundred pupils, acting as co-searchers, have been thinking about certain topics such as cerebral plasticity, intelligence and the role of memory, in the context of the production of written work. They have been deep inside their brains, they have built up their own metacognitive tools, in order to learn how to regulate themselves and how to regulate one another, while doing their written work. The effects of this module on the production of written work have been measured both quantitatively and qualitatively, and they have reflected the importance of learning how to regulate oneself on an affective and cognitive level. In so doing, the pupils have been able to get to know themselves better, and they have grown in maturity, in autonomy and humanity, becoming « co-adventurers of their brains », specially when they have to write essays based on imagination. Therefore, this article aims at presenting this study, examining the issues, the challenges, the precautions to take into account in such a research. It ends with the importance of considering student support not only on an intellectual level but on a social, affective level too, as well as in terms of relation.